The Mortara Affair and the Question of Thomas Aquinas’s Teaching Against Forced Baptism - Tapie, Matthew (Studies in Christian-Jewish Relations, 2019)
Contemporary scholars critical of Pope Pius IX’s decision to remove Edgardo Mortara from his parents in Bologna, Italy, in 1858, appeal to Thomas Aquinas’s teaching against forced baptism of Jewish children in the Summa theologiae. However, these scholars have overlooked the fact that the question of Aquinas’s teaching against forced baptism was actually at the center of a rather extensive theological exchange between the Mortara family, and the Vatican’s papal counsel in 1858. This article demonstrates that without attention to the 1858 exchange, the contemporary debate lacks an understanding of the key theological questions, including the problem that Aquinas’s teaching was claimed by both sides. After an analysis of the appeals to Aquinas in the 1858 exchange, the article demonstrates why the contemporary discussion could benefit from a closer examination of Aquinas’s teaching against forced baptism of Jewish children in its historical context.